Skeletal Muscle Fibre-Specific Knockout of p53 Does Not Reduce Mitochondrial Content or Enzyme Activity - Stocks, Ben; Dent, Jessica R.; Joanisse, Sophie; McCurdy, Carrie E.; Philp, Andrew (Frontiers in Physiology, 2017)
Tumour protein 53 (p53) has been implicated in the regulation of mitochondrial biogenesis in skeletal muscle, with whole-body p53 knockout mice displaying impairments in basal mitochondrial content, respiratory capacity and enzyme activity. This study aimed to determine the effect of skeletal muscle-specific loss of p53 on mitochondrial content and enzyme activity. Mitochondrial protein content, enzyme activity and mRNA profiles were assessed in skeletal muscle of eight-week-old male muscle fibre-specific p53 knockout mice (p53 mKO) and floxed littermate controls (WT) under basal conditions. p53 mKO and WT mice displayed similar content of electron transport chain proteins I-V and citrate synthase enzyme activity in skeletal muscle. In addition, the content of proteins regulating mitochondrial morphology (MFN2, mitofillin, OPA1, DRP1, FIS1), fatty acid metabolism (β-HAD, ACADM, ACADL, ACADVL), carbohydrate metabolism (HKII, PDH), energy sensing (AMPKα2, AMPKβ2) and gene transcription (NRF1, PGC-1α and TFAM) were comparable in p53 mKO and WT mice (p > 0.05). Furthermore, p53 mKO mice exhibited normal mRNA profiles of targeted mitochondrial, metabolic and transcriptional proteins (p > 0.05). Thus it appears that p53 expression in skeletal muscle fibres is not required to develop or maintain mitochondrial protein content or enzyme function in skeletal muscle under basal conditions.